Pemberdayaan Masyarakat Nambo: Edukasi Budidaya Sistem Bioflok dan Peningkatan Keterampilan Diversifikasi Produk Lele - Agustin Patmawati; Jeremias Diotama; Muhammad Irfan Khadafi; Warcito Warcito (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Institut Pertanian Bogor, 2020)
Catfish is one of the cultivation commodities. The advantages of catfish include fast growth and have the ability to adapt to a high environment. Biofloc technology is a technology to use both heterotrophic and autotrophic bacteria that can intensively convert organic waste into flock-shaped microorganisms, which can then be utilized by fish as a food source. Nambo villagers have not been much in the cultivation of catfish. The development of fish farming, especially catfish needs to be developed, considering that catfish farming does not require intensive care and a lot of good nutrition in catfish that is needed by the human body. Fish nuggets are processed products from ground meat, given spices and mixed with binder. Then printed into a certain shape according to taste, dipped in batter and breading then fried or before frying can be stored in the freezer first. The method of this socialization activity uses two different methods according to the session of the event carried out. The session was carried out namely the making session of catfish nuggets and the session of delivering material about catfish cultivation with a biofloc system. The method used in the catfish nugget making session is the demonstration method. The material delivery session on catfish farming using the biofloc system is using the socialization method by inviting Mrs. Titi who is a biofloc catfish cultivator from Kembang Kuning Village. This socialization activity got results, namely the Village Community of Nambo especially the housewives got some knowledge. Knowledge of catfish farming with a biofloc system, skills in making nuggets from catfish and catfish fillet techniques well. Keywords: biofloc system, catfish, demonstration